Spontaneous Pneumothorax due to Ectopic Deciduosis: A Case Report - Dudek, Wojciech; Schreiner, Waldemar; Strehl, Johanna; Sirbu, Horia (The Thoracic and Cardiovascular Surgeon Reports, 2014)
This report presents a 20-week pregnant 38-year-old woman with right-sided pneumothorax due to pulmonary deciduosis. Initial pleural drainage was ineffective. Video-assisted thoracoscopy revealed areas of consolidation within the lung parenchyma. A wedge resection with partial pleurectomy was performed. Histopathological examination showed subpleural decidual implants. The patient made a full recovery and was discharged on day 5. Videoscopic inspection of the lung parenchyma and pleura with resection of decidual foci is the recommended treatment for pneumothorax in pregnant women with pleuropulmonary deciduosis in whom classical pleural drainage is ineffective.
Keywords: pleuropulmonary ectopic deciduosis; spontaneous pneumothorax; thoracoscopic surgery